2010
DOI: 10.1111/j.1439-0523.2009.01753.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity in hazelnut (Corylus avellanaL.) cultivars from Black Sea countries assessed using SSR markers

Abstract: European hazelnut (Corylus avellana L.) is an important crop in Turkey, Georgia and Azerbaijan, where cultivars were selected from the native vegetation. Accessions from Turkey have been assigned to the Black Sea group, and cultivars from Georgia and Azerbaijan have a similar phenotype. Genetic diversity was investigated in 88 accessions from these three countries and compared with cultivars from Spain and Italy using 12 microsatellite loci. A high level of genetic diversity (H e = 0.71, H o = 0.70) was observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
30
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 33 publications
5
30
0
2
Order By: Relevance
“…Whilst there have been several studies on C. avellana, the present study is the first to look at natural populations of hazel using high-resolution, codominant nuclear microsatellite markers, in contrast with those which have used low resolution and/or dominant markers (allozymes and amplified fragment length polymorphisms (AFLPs)) or those which have focused on the genetics of cultivated varieties. Two allozyme studies, one of which examined populations from central to northern Europe (Persson et al 2004) and another which used samples mainly not only from Germany but also from Italy and Hungary (Leinemann et al 2013), found similar levels of genetic diversity, measured by both number of alleles (A) and expected heterozygosity (H E ) Although it is not possible to draw meaningful comparisons between levels of diversity observed in the present study with those calculated from allozymes in natural populations, it is possible to contrast these levels with those observed in cultivated varieties and landraces based on microsatellites, which were lower and ranged from H E = 0.71 to H E = 0.78 (Boccacci et al 2006;Gökirmak et al 2009;Boccacci and Botta 2010;Gürcan et al 2010b;Campa et al 2011;Boccacci et al 2013). In contrast, all but one sample analysed here had an H E >0.8 (Table 1).…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…Whilst there have been several studies on C. avellana, the present study is the first to look at natural populations of hazel using high-resolution, codominant nuclear microsatellite markers, in contrast with those which have used low resolution and/or dominant markers (allozymes and amplified fragment length polymorphisms (AFLPs)) or those which have focused on the genetics of cultivated varieties. Two allozyme studies, one of which examined populations from central to northern Europe (Persson et al 2004) and another which used samples mainly not only from Germany but also from Italy and Hungary (Leinemann et al 2013), found similar levels of genetic diversity, measured by both number of alleles (A) and expected heterozygosity (H E ) Although it is not possible to draw meaningful comparisons between levels of diversity observed in the present study with those calculated from allozymes in natural populations, it is possible to contrast these levels with those observed in cultivated varieties and landraces based on microsatellites, which were lower and ranged from H E = 0.71 to H E = 0.78 (Boccacci et al 2006;Gökirmak et al 2009;Boccacci and Botta 2010;Gürcan et al 2010b;Campa et al 2011;Boccacci et al 2013). In contrast, all but one sample analysed here had an H E >0.8 (Table 1).…”
Section: Discussionmentioning
confidence: 45%
“…All samples were genotyped for seven nuclear microsatellites (A604, A605, A613, A614, B671, B767, B791), which had previously been developed for use in European hazelnut (Gürcan et al 2010a). PCR was carried out in a total volume of 10 μl containing 100 ng genomic DNA, 5 pmol of 6-FAM-labelled M13 primer, 0.05 pmol of each M13-tailed forward primer, 5 pmol each reverse primer, 1× PCR reaction buffer, 200 μM each dNTP, 2.5 mM MgCl 2 and 0.25 U GoTaq Flexi DNA polymerase (Promega, Sunnyvale, CA, USA).…”
Section: Genotypingmentioning
confidence: 99%
“…The study of the genetic relationships and population structure among wild forms, landraces, and cultivars in a geographic area can supply information about the putative domestication events, the evolutionary relationship, or the gene flow between them. According to several authors Botta 2009, 2010;Gökirmak et al 2009;Gürcan et al 2010), C. avellana seems to have been domesticated independently in six different areas: British Islands, central Europe, Spain, Italy, Black Sea, and Iran. The results reported by Boccacci et al (2013) are in agreement with these conclusions, indicating the existence of three main germplasm groups in the Mediterranean basin which could correspond with three domestication areas: northeastern Spain (Catalonia) and southern Italy (Campania) in the West and the Black Sea region in the East.…”
Section: Genetic Characterization Of Landracesmentioning
confidence: 99%
“…The main result obtained from this survey was that in many collection fields are conserved the same cultivars, indicating the need to rationalize genetic resources and that few efforts were made to include new accessions in the collections. For example, the NCGR and Oregon State University have increased efforts to collect cultivated and wild accession of Corylus, such as from the Balkans, Russia and Caucasus, and now in their collections there are more than 700 accessions, including all major Corylus species (Gürcan et al 2010). However, a number of species are still lacking, especially when considering their wide geographic range, for these reasons recovering and evaluation efforts are still needed manly in Europe.…”
Section: Morphological Evaluation Of Hazelnut Accessionsmentioning
confidence: 99%
See 1 more Smart Citation